Integrated multi-omics analysis reveals key hub genes and mechanisms in calcific aortic stenosis - Wang, Feng-Xia; Liu, Shuai; Guo, Hao-Qiang; Yu, Jia-Qing; Cui, Jun; Cheng, Qi; Aisikeer, Nilupaer; Liu, Fen; Duan, Ming-Jun; Xie, Xiang; Ma, Yi-tong (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveAortic stenosis (AS) is a critical risk factor for the development of structural heart disease, and identifying its pathogenic genes will provide new insights into cardiac pathology and treatment.Methods“edgeR” was used to calculate differentially expressed genes (DEGs) for bulk-RNAseq. GO, KEGG, and GSEA analyses were performed on the DEGs. Aortic valves from 8 AS patients and 8 non-AS patients were collected for proteomic sequencing. After DEG analysis, five algorithms were used to identify hub genes. ROC curves were constructed for the hub genes. Single-cell RNA sequencing (scRNAseq) was applied to systematically elaborate the mechanism in AS pathogenesis.ResultsTranscriptome data showed that AS was accompanied by high expression of genes such as MMP9, CXCL8, and SPP1, with significant activation of hypoxia, inflammatory response, and fibrosis. Proteomic sequencing of calcified AS revealed significantly enhanced hypoxic response, TNF-α signaling, and extracellular matrix (ECM) formation. Sixteen hub genes, including ITGB3, ITGAV, and MMP9, were identified by five algorithms, all with high diagnostic efficacy (AUC > 0.75). PCR experiments confirmed that MMP9 and PLAU were highly expressed in calcified aortic valves (P < 0.05). scRNAseq revealed that in highly calcified regions, MMP9 and PLAU were mainly distributed in endothelial cells, monocytes, and macrophages, participating in the differentiation of monocytes and macrophages and relating to lipid metabolism and proinflammatory responses.ConclusionThe 16 hub genes can assist in the diagnosis of aortic stenosis, and MMP9 and PLAU may participate in AS development by regulating the proinflammatory effects of monocytes and macrophages.